2021
DOI: 10.3390/molecules26040872
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Mg–Al Order-Disorder Reaction in MgAl2O4-Spinel: Constrained by Prolonged Annealing Experiments at 773–1123 K

Abstract: MgAl2O4-spinel has wide industrial and geological applications due to its special structural and physical–chemical features. It is presumably the most important endmember of complex natural spinel solid solutions, and therefore provides a structural model for a large group of minerals with the spinel structure. There exists a well known but still inadequately understood phenomenon in the structure of MgAl2O4-spinel, the Mg–Al cations readily exchanging their positions in response to variations of temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Lattice parameters of MgAl 2 O 4 spinel at ambient pressure conditions have been measured using X-ray diffraction [19,20,22,23] and neutron diffraction [24][25][26] from room temperature to ~1900 K, and the values at the low-temperature range were provided by Grimes and Al-Ajaj [21] (Table 1, Figure 1). Although previous investigations reported that the order-disorder transition would affect the volume as well as the thermal expansion of MgAl 2 O 4 spinel [11,17,20,[43][44][45], due to the limitations of the method used in this study, we assume that the ordering state of the cations does not affect the volume. Therefore, we converted the lattice parameters of MgAl 2 O 4 spinel from the published literature [19][20][21][22][23][24][25][26] (Table 1) to the unit-cell volumes, then analyzed the values via the EoSfit software [46] and fit them using the empirical formula recommended by Fei [47].…”
Section: Calculation Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…Lattice parameters of MgAl 2 O 4 spinel at ambient pressure conditions have been measured using X-ray diffraction [19,20,22,23] and neutron diffraction [24][25][26] from room temperature to ~1900 K, and the values at the low-temperature range were provided by Grimes and Al-Ajaj [21] (Table 1, Figure 1). Although previous investigations reported that the order-disorder transition would affect the volume as well as the thermal expansion of MgAl 2 O 4 spinel [11,17,20,[43][44][45], due to the limitations of the method used in this study, we assume that the ordering state of the cations does not affect the volume. Therefore, we converted the lattice parameters of MgAl 2 O 4 spinel from the published literature [19][20][21][22][23][24][25][26] (Table 1) to the unit-cell volumes, then analyzed the values via the EoSfit software [46] and fit them using the empirical formula recommended by Fei [47].…”
Section: Calculation Proceduresmentioning
confidence: 98%
“…that the order-disorder transition would affect the volume as well as the thermal expansion of MgAl2O4 spinel [11,17,20,[43][44][45], due to the limitations of the method used in this study, we assume that the ordering state of the cations does not affect the volume. Therefore, we converted the lattice parameters of MgAl2O4 spinel from the published literature [19][20][21][22][23][24][25][26] (Table 1) to the unit-cell volumes, then analyzed the values via the EoSfit software [46] and fit them using the empirical formula recommended by Fei [47].…”
Section: S(t)mentioning
confidence: 99%